(3QSGdI aj UMI hbajI GdOQGge hGdOfGfjQs - (3CHh GdSYhOs
(3ChdgG (B:s
(3hHYO aGYde Cf hba Gdefbhd JHYkG dYbGQ chba GdHfGA s
(3BNQgG (B:s
(3JeJ GdQSGdI GdeDOjI Edi Gdehdi GdeYghO Hjf GdehGdi GdeTghQ HCHj GdSYhO s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI HOeTb (B(9303) s
Keywords: (3Gdabg GdMfajs